PENYUSUNAN MATERI KETRAMPILAN SOSIAL KELAS X7 SMA NEGERI 5 PEKANBARU TAHUN AJARAN 2013/2014 - Sri Utami; Zulfan Saam; Abu Asyari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abtract: The lack of social capability and matter’s sources are being the main case for the researcher to make a research about the compliation of social capability matter for the students at SMA Negeri 5 Pekanbaru 2013/2014, especially for those who are at class X7. The purposes of this research are : 1) To make a complete explanation about social capability matter which is compatible for students based on systematic, pictures, the upgrade and the completeness explanation for the matter. 2) To get the quality the matter. Which using research method and development. For this research, there are some trusted people who validated the data, they are guide lecturer, the second guide lecturer, a lecturer of BK FKIP UR, caretaker teacher, 6 persons friends and also 35 students at SMA Negeri 5 Pekanbaru 2013/2014 on class X7. There are 5 sub topics of the matter, 1). Definition of social capability, 2). Kinds of social capability, 3). Factors with included social capability, 4). The importance of social capability education, 5). Effort to the develop social capability. The quality of social capability matter with has been made based on clearness matter is very clear exsplained with X=4,44 and the percentage has reached 88,88%. Systematic aspect of the matter is systematic with X=4,13 and the percentage has reached 82,66 % . The aspect of picture to support the matter is good with X= 4,15 and the percentage has reached 83,11%. The aspect of upgraded matter is upgraded with X=4,04 and the percentage reached 80,88%. The aspect of completeness matter is very complete with X=4.51 and the percentage has reached 90.22%. And of the aspects has a very good quality with X=4,25 and the percentage has reached 85,15%.Key Words: Matter social capability